Uptake of Cervical Cancer Screening Among Female Staff at the University College Hospital, Ibadan - A.E, Adetona; K.O, Osungbade; O.O, Akinyemi; T.A, Obembe (Journal of Cervical Cancer, 2019)
Background This study aim to assess the factors affecting uptake of cervical cancer screening programmes among female staff of the University College Hospital (UCH), Ibadan in 2014. Method A descriptive cross-sectional study involving 375 participants selected using a stratified random sampling technique with proportional allocation to population size and interviewed using a pre-tested self-administered semi-structured questionnaire. Information on their basic knowledge on cervical cancer were scored to determine good knowledge. Patients’ attitudes toward cervical cancer screening as well as factors affecting uptake were also assessed. Data analysis was done in 2014 using descriptive statistics while screening uptake predictors were determined using logistic regression at p ≤0.05. Results Completed questionnaires were returned by 360 respondents; 13.3% were clinical while 86.7% were non-clinical staff of age range 20 to 58 years (38.2±0.42 years). Majority of the respondents, (95.5%), had heard about cervical cancer with 61.9% having “good knowledge”, but only few (34.2%) had been screened. Averagely, 47.5% displayed positive attitude to cervical cancer screening with Pap smear being the most reported screening procedure. The common barriers to screening uptaking include indecision, inadequate information and feeling of good health. Others were staff hostility, lack of privacy, and cost. Using logistic Regression at p ≤0.05, females with negative attitude and those with children were less likely to uptake cervical cancer screening services. Conclusion The knowledge-uptake gaps of cervical cancer screenings were high as revealed in this study. Therefore, there is a need to further educate eligible women on uptake of cervical cancer screening.
Keywords: Cervical screening; Female health workers